2007
DOI: 10.3892/ijo.30.4.919
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of XIAP expression in renal cell carcinoma predicts a worse prognosis

Abstract: Abstract. X-linked inhibitor of apoptosis protein (XIAP) is the most potent caspase-inhibitory IAP family member and a negative regulator of various apoptotic stimuli. Thus, XIAP overexpression in cancer cells may select for tumor cell survival following various cytotoxic therapeutic modalities. The anatomical staging system in renal cell carcinoma (RCC) currently provides good prognostic information, albeit insufficient. We hypothesize that overexpression of XIAP in RCC may serve as a molecular prognostic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 24 publications
3
57
1
Order By: Relevance
“…Increased expression of XIAP has been observed in many human cancers, including prostate, lung and acute/chronic leukemia (Ferreira et al, 2001;Krajewska et al, 2003;Schimmer et al, 2003). Furthermore, its expression has been correlated with a worse prognosis in bladder carcinoma, renal cell carcinoma and acute myloid leukemia (Tamm et al, 2004;Li et al, 2007;Mizutani et al, 2007). Earlier studies have shown that HCT116 or DLD-1 cells in which XIAP expression has been downregulated exhibit increased caspase 3 cleavage and apoptosis in response to TRAIL (Cummins et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of XIAP has been observed in many human cancers, including prostate, lung and acute/chronic leukemia (Ferreira et al, 2001;Krajewska et al, 2003;Schimmer et al, 2003). Furthermore, its expression has been correlated with a worse prognosis in bladder carcinoma, renal cell carcinoma and acute myloid leukemia (Tamm et al, 2004;Li et al, 2007;Mizutani et al, 2007). Earlier studies have shown that HCT116 or DLD-1 cells in which XIAP expression has been downregulated exhibit increased caspase 3 cleavage and apoptosis in response to TRAIL (Cummins et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of XIAP has been demonstrated in cancers of various origins. [10][11][12][13][14][15][16] Not only is XIAP overexpressed in cancer, increased XIAP expression has been shown to contribute to apoptosis resistance and conversely, XIAP antagonism sensitizes cancer cells to multiple types of apoptotic stimuli in vitro and in vivo. 13,[17][18][19][20][21][22][23][24][25]28,[32][33][34][35][36][37] These apoptotic stimuli have included various chemotherapeutic agents, ionizing radiation, tumor necrosis factor-related apoptosis-inducing ligand, anoikis induction and immune clearance by cytotoxic lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…21,[23][24][25] Consistent with an antiapoptotic role, high levels of XIAP have an adverse prognosis in certain cancers. 14,15 However, there was an unexpected favorable prognosis seen in prostate and non-small cell lung cancers with high levels of XIAP expression. 12,26 We thus chose to further examine the role of XIAP in a tumor model that would resemble human cancer more closely than xenograft or in vitro studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] XIAP expression correlates with clinical aggressiveness in acute myelogenous leukemia, diffuse large B-cell lymphoma and renal cell carcinoma. [12][13][14] XIAP is expressed in some normal tissues; 15 however, XIAP-knockout mice lack any significant pathology, suggesting normal cells function properly in its absence. For all of the above reasons, XIAP is considered an attractive target for drug discovery.…”
mentioning
confidence: 99%